Thermal performance of ultra-thin flattened heat pipes - Zhou, Wenjie; Xie, Peida; Li, Yong; Yan, Yuying; Li, Bo (Elsevier, 2017)
This study investigates the thermal performance of composite ultra-thin heat pipes (UTHPs). UTHPs are fabricated by flattening cylindrical heat pipes with outer diameter of 2 mm. The thickness and width were 0.8 mm and 2.7 mm, respectively. The composite wick structure is made of sintered copper foam-mesh wick (CFMW). CFMW combines the good heat transfer performance of copper foam and the high mechanical strength of mesh. The manufacturing process of UTHP was studied and the thermal performance of UTHP samples were investigated experimentally. The results indicate that the optimum filling ratio of UTHPs is 100% and the maximum temperature difference is 3.7 °C under the maximum heat transport capacity of 5 W. The thermal resistances of UTHPs increase gradually with the heat power before drying out. Too low or too high filling ratios will reduce the heat transfer efficiency of UTHPs by increasing the thermal resistances. With the optimum filling ratio of 100%, the evaporation thermal resistance of UTHP is found to be 0.29 K/W and the condensation thermal resistance is 0.45 K/W at the heat load of 5 W.